Audit Committee Strength and Environmental Tax Transparency in Dampening PublicFraud Perceptions in ASEAN - Laras Angelia Nirwana Sari; M. Syahrudin (Inovasi Analisis Data, 2025)
Purpose – This research explores the dynamic influences of fraud-related behavioral drivers alongside taxation governance and audit oversighton anti-fraud intentions.Design/methodology/approach – Based on a multilevel framework, the structural model of perceptions combines fraud behavior with taxgovernance mechanisms and audit oversight.Findings – Results demonstrate that fraud drivers, perceived tax transparency and environmental tax compliance orientation are not likely tohave both direct and indirect influences on anti-fraud intention. Objectively speaking, the mechanisms of oversight embedded in audit qualityalso fail to moderate these associations. The presence of formal governance systems and transparency tools is not enough to activate fraudawareness into intention to prevent behavior when enforcement credibility and personal contribution are minimized.Originality/value – The paper provides a unique combination of fraud behavioral theory, taxation governance and audit oversight in anintegrated framework and presents data-based discussions on the limitations of formal controls in perception-based anti-fraud environments.Research implications – The results suggest that there is a need for theoretical expansion by including enforcement salience, institutionaltrust and moral engagement to further understand anti-fraud behaviour not only as the result of structural governance mechanisms.